(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Chronic obstructive pulmonary disease (COPD) and ischemic heart disease (IHD) are among the most prevalent chronic conditions globally, frequently coexisting due to shared risk factors such as smoking, aging, systemic inflammation, and endothelial dysfunction (Divo et al., 2012). The interplay between these diseases significantly increases the risk of multiorgan complications, including renal impairment.